Fertilizantes nitrogenados en el desarrollo y producción en el cultivo de arroz (Oryza sativa L.), en el cantón Babahoyo - León Guerra, Kevin Oswaldo (2020)
The present work was carried out in order to have an information base on the use of nitrogenous fertilizers, which carry certain risks if we carry out applications excessively in the crop, and for this, its effects and conditions must be kept in mind when applying. since knowing these factors can thus be used to the best advantage knowing in what conditions and when it should be applied. The analysis of this project determined that the use of nitrogenous fertilizers are a necessary and indispensable source in the production of the rice crop and which must be taken into account that they can generate contaminating, harmful and noticeable effects on the soils, for which The aim is to ensure that rice producers through an information document, continuous training and implementation of technologies and methods such as soil analysis, nutritional requirements of rice cultivation and the stages in which they are required to achieve good development, reduce these Long-term effects. With this, achieving good production, generating higher economic income and gaining a better knowledge of balanced fertilization.